A mobile magnetic pad with fast light-switchable adhesion capabilities. (3rd August 2021) - Su, Lin; Jin, Dong Dong; Pan, Cheng Feng; Xia, Neng; Chan, Kai Fung; Iacovacci, Veronica; Xu, Tiantian; Du, Xuemin; Zhang, Li
Abstract: Octopus suckers that possess the ability to actively control adhesion through muscle actuation have inspired artificial adhesives for safe manipulation of thin and delicate objects. However, the design of adhesives with fast adhesion switching speed to transport cargoes in confined spaces remains an open challenge. Here, we present an untethered magnetic adhesive pad combining the functionality of fast adhesion switching and remotely controlled locomotion. The adhesive pad can be activated from low-adhesion state to high-adhesion state by near infrared laser within 30 s, allowing to fulfill a high-throughput task of retrieving and releasing objects. Moreover, under the guidance of external magnetic field, the proposed pad is demonstrated to transport thin and fragile electronic components across a tortuous path, thus indicating its potential for dexterous delivery in complex working environments.